The coloring mechanism of a novel golden variety in Populus deltoides based on the RGB color mode - Yuru Tian; Shupei Rao; Qianqian Li; Meng Xu; Aike Wang; Hechen Zhang; Jinhuan Chen (Forestry Research, 2021)
Compared to flower color and red leaf mutants, the mechanism of yellow leaf formation in woody plants is more complicated and less understood. Poplars are common and widely distributed perennial trees. Here, we obtained a golden leaf mutant poplar variety (JHY) and compared it with its original green leaf poplar (Populus sp. Linn. ‘2025’) in terms of phenotype, pigment content, the transcriptomes and metabolomes. Through transcriptome sequencing, we found that the chlorophyll degradation genes, and the genes in anthocyanin metabolism in JHY were up-regulated compared to L2025 and the carotenoid synthesis genes were down-regulated. Further based on HPLC-ESI-MS/MS technology, 16 differentially expressed anthocyanins were identified, 14 reddish anthocyanins of which were significantly up-regulated. According to these results, we proposed a coloring mechanism of JHY based on the RGB color mode. The yellow color of carotenoids and the red color of anthocyanins overlay each other, combined with a reduction in chlorophyll, turning the leaves golden. This study systematic analyzes the causes of golden leaf formation through the omics integration approach, which will provide reference for the breeding of golden leaf trees.